Diabetes Prevalence and Its Association with IDRS among Patients’ Attendees of Tertiary Care Centre of Jabalpur District of Madhya Pradesh - Dr. Pradeep kasar, Dr. AdityaThakur, Dr. Neelam Anupama Toppo, Dr. Vishnu Gupta (International Journal of Innovative Research in Medical Science, 2017)
Introduction: Diabetes also known as a "silent disease," exhibiting no symptoms until it progresses to severe target organ damage. Because of increasing burden of the diabetes and its iceberg nature, active and opportunistic effort was attempted for early diagnosis of diabetes by means of screening with the objectives to find out the prevalence and the risk of diabetes mellitus among patients' attendees of tertiary care hospital by using Indian diabetes risk score and to estimate the usefulness of the Indian diabetes risk score for detecting undiagnosed diabetes among patients' attendees of tertiary care hospital. Methodology: A cross sectional study was conducted in a tertiary care hospital during April to July 2016 among attendees of patients who were aged more than 30 years. 406 individuals were screened for Diabetes using IDRS score and Random Blood Sugar. Result: Overall prevalence was found 8.6%, with maximum in males (12.68%) as compared to female (4.47 %) (Chi sqaure= 7.664, df =1, two tailed ρ value= 0.0056). Age specific prevalence was maximum in 61-70 years of age group (13.46 %) and minimum in 30-40 years of age group (4.37%). It was observed that mean blood sugar was increased significantly with low risk individuals to high risk individuals. More than half (57.63%) individuals were in high risk category followed by individuals with moderate risk (37.43%) and low risk i.e. only 4.92% individuals. Obesity, Lack of exercise, family history has been identified as significant risk factors for occurrence of Diabetes. An IDRS of less than 60 was optimal for identifying non-T2DM and ≥60 for identifying T2DM (AUC, 0.727; CI, 0.663–0.792; sensitivity, 79.9%; specificity, 83.8%). Conclusion: Family history of diabetes and obesity was found as risk factors which significantly contributed in occurrence of Diabetes. IDRS is very useful cost effective tool to detect undiagnosed diabetes in the community and also as very good risk indicator for Diabetes.